The Effect of Microhabitat Diversity on the Similarity of Soil Insect Types at Lombok Island, Indonesia - Immy Suci Rohyani (Jurnal Penelitian Pendidikan IPA, 2021)
Soil insects are a group of organisms whose existence is highly dependent on their microhabitat. Its presence is indispensable because of its ability to reform and decompose organic matter. The presence of soil insects illustrates the functioning of a habitat. This study aims to analyze abiotic and biotic environmental conditions in several types of soil insect habitats on the island of Lombok and securitize the level of similarity of insect species in each of these habitats. The research method used in determining the initial sample point in each habitat is purposive sampling. The parameters observed are those thought to influence the presence of soil insects, including parameters of the abiotic environment and parameters of the biotic environment. The results obtained were that the soil insects found in forest, garden, mangrove, and mining habitats had a high degree of similarity. Forest and garden habitats have a preferred micro-habitat because of the high levels of organic C, moisture, total N, and neural soil pH as environmental factors that most support the existence of soil insects